Citrullinated vimentin presented on MHC-II in tumor cells is a target for CD4+ T-cell-mediated antitumor immunity - Brentville, Victoria A.; Metheringham, Rachael L.; Gunn, Barbara; Symonds, Peter; Daniels, Ian; Gijon, Mohamed; Cook, Katherine; Xue, Wei; Durrant, Lindy (American Association for Cancer Research, 2016)
Stressful conditions in the harsh tumor microenvironment induce autophagy in cancer cells as a mechanism to promote their survival. However, autophagy also causes post-translational modification of proteins that are recognized by the immune system. In particular, modified self-antigens can trigger CD4(+) T-cell responses that might be exploited to boost antitumor immune defenses. In this study, we investigated the ability of CD4 cells to target tumor-specific self-antigens modified by citrullination, which converts arginine residues in proteins to citrulline. Focusing on the intermediate filament protein vimentin, which is frequently citrullinated in cells during epithelial-to-mesenchymal transition of metastasizing epithelial tumors, we generated citrullinated vimentin peptides for immunization experiments in mice. Immunization with these peptides induced IFNγ- and granzyme B-secreting CD4 T cells in response to autophagic tumor targets. Remarkably, a single immunization with modified peptide, up to 14 days after tumor implant, resulted in long-term survival in 60% to 90% of animals with no associated toxicity. This antitumor response was dependent on CD4 cells and not CD8(+) T cells. These results show how CD4 cells can mediate potent antitumor responses against modified self-epitopes presented on tumor cells, and they illustrate for the first time how the citrullinated peptides may offer especially attractive vaccine targets for cancer therapy.